2023
DOI: 10.1021/acssuschemeng.2c06698
|View full text |Cite
|
Sign up to set email alerts
|

Pine Needles as a Biomass Resource for Phenolic Compounds: Trade-Off between Efficiency and Sustainability of the Extraction Methods by Life Cycle Assessment

Abstract: Polyphenols are natural organic compounds with many possible applications because of their unique biological activities. They can be extracted from a wide variety of waste biomasses, and a great deal of interest exists in identifying extraction processes optimized in terms of both yield and environmental impact. In this framework, we have compared three techniques, namely, maceration and extraction assisted by either ultrasounds or microwaves, for the extraction of phenolic compounds from dry pine needles, lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Replacing the acetone solvent with ethanol might make the extraction step greener but it makes the total harm of the process worse because it lowers the yield of extract. 4 For indirect hotspots, improving the yield or purity is a higher priority than reducing the harm caused by the step.…”
Section: The Types Of Hotspotsmentioning
confidence: 99%
“…Replacing the acetone solvent with ethanol might make the extraction step greener but it makes the total harm of the process worse because it lowers the yield of extract. 4 For indirect hotspots, improving the yield or purity is a higher priority than reducing the harm caused by the step.…”
Section: The Types Of Hotspotsmentioning
confidence: 99%
“…From lignans in needle aqueous extracts, taxiresinol, lariciresinol, pinoresinol, secoisolariciresinol, and hydroxymataresinol have been identified [59,61,67,68]. It has also been observed that the extraction of polyphenolic compounds from coniferous needles is affected by the preparation of the raw material and extraction conditions [58,68]. Comparing freeze-drying, vacuum-drying, and natural air-drying, freeze-drying yields the highest amount of polyphenol compounds.…”
Section: Water-soluble Components Of Coniferous Needles/greenerymentioning
confidence: 99%
“…The recovery of phenolic compounds from forest waste biomass is gaining considerable attention [49][50][51], and the choice of the method and solvent used for extraction is a particularly important step [52]. Traditional extraction methods, such as maceration, Soxhlet extraction, and percolation, lead to low extraction yields, require relatively large quantities of solvents, and are often time-consuming [53].…”
Section: Introductionmentioning
confidence: 99%